Sustainability of Mahogany Production in Plantations: Does Resource Availability Influence Susceptibility of Young Mahogany Plantation Stands to Hypsipyla robusta Infestation? - C. B. Darko; E. Opuni-Frimpong; S. A. Owusu; B. Kyere; A. J. Storer (International Journal of Forestry Research)
Hypsipyla robusta Moore (Lepidoptera: Pyralidae), like many other moth species, shows selectivity when choosing host plants for its eggs. Four Meliaceae species (Khaya grandifoliola, K. ivorensis, Swietenia macrophyla, and Entandrophragma cylindricum) were established in a moist semideciduous forest in Ghana to study this selectivity at 12 and 21 months after planting. The analysis of variance (ANOVA) at a P-value of 0.05 was used to test the significance of differences in infestation by H. robusta between the species. H. robusta attacks were recorded by month 12 after planting in the field, and only Khaya spp. was attacked, with attacks evident on 15.5% of K grandifoliola and 6.6% K. ivorensis. Saplings in blocks closer to an older H. robusta infested K. grandifoliola stand had more infestation compared to saplings further away. The mean percentage of K. grandifoliola attacked was 38.9%, 38.9%, 13.3%, and 7.4% in 4 different plots located increasingly further away from the older infested plantation. A similar trend was found in K. ivorensis with 28.4%, 7.1%, 0.0%, and 0.0% in the plots located increasingly further away from the infested stand. These results indicate a higher number of shoot borer attacks at the edge of the plantation and in proximity to other infested plantations. After 21 months, the fastest-growing species and the fastest-growing individuals within the species were the most infested. K. grandifoliola recorded the fastest growth and most attacks followed by K. ivorensis and S. macrophylla. E. cylindricum recorded the least growth and no H. robusta infestation. After 21 months, the mean percentages of trees attacked were 59.1%, 23.7%, 5.6%, and 0.0% for K. grandifoliola, K. ivorensis, S. macrophylla, and E. cylindricum, respectively. Within species, the fastest-growing saplings experienced the most attacks. A positive correlation was observed between the plant size and H. robusta attacks (R2 = 0.76). Attacks resulted in the death of the apical shoot and the proliferation of multiple shoots in only the Khaya spp., with K. ivorensis recording a lower number of shoots than K. grandifoliola. These proliferated shoots were also attacked, and a positive correlation was observed between the number of proliferated shoots and H. robusta attacks (R2 = 0.84). These findings will assist plantation developers, forest managers, and investors in mahogany plantations to devise integrated pest management strategies to reduce the impact of Hypsipyla attacks on their plantations.